Amplifiers : how great leaders magnify the power of teams, increase the impact of organizations, and turn up the volume on positive change /: how great leaders magnify the power of teams, increase the impact of organizations, and turn up the volume on positive change. (2021) - Finegan, Tom
No abstract available